2015
DOI: 10.4067/s0034-98872015000400002
|View full text |Cite|
|
Sign up to set email alerts
|

Barreras de acceso a tratamiento de la depresión posparto en Centros de Atención Primaria de la Región Metropolitana: un estudio cualitativo

Abstract: (Rev Med Chile 2015; 143: 424-432)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
16
0
8
Order By: Relevance
“…Organisation-level barriers include lack of a specific MHCS to turn to for PPD treatment, lack of availability of MHCS in their villages, long wait times for appointments with a psychiatrist or psychologist, and long travel distance to health facilities. Rojas et al, (2015) found similar barriers associated with access to MHCS among women with PPD in Chile, including lack of knowledge about PPD, lack of available treatment options, poor network support, long wait times, and lack of coordination between clinical and administrative decisions (Rojas et al, 2015). Nakku et al (2016) suggest that in order to increase access to MHCS, primary HCSs need to make appropriate MHCSs available to suit users' needs (Nakku et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Organisation-level barriers include lack of a specific MHCS to turn to for PPD treatment, lack of availability of MHCS in their villages, long wait times for appointments with a psychiatrist or psychologist, and long travel distance to health facilities. Rojas et al, (2015) found similar barriers associated with access to MHCS among women with PPD in Chile, including lack of knowledge about PPD, lack of available treatment options, poor network support, long wait times, and lack of coordination between clinical and administrative decisions (Rojas et al, 2015). Nakku et al (2016) suggest that in order to increase access to MHCS, primary HCSs need to make appropriate MHCSs available to suit users' needs (Nakku et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to treatment of PPD were evidenced by a study in Chile, such as lack of user knowledge about the disease, negative conceptualization and rejection of the available treatment options; poor network support and long waiting times and a lack of coordination between clinical and administrative decisions 53 .…”
Section: Postpartum Depression (Ppd): Non-specialized Management In Phcmentioning
confidence: 99%
“…Se llevaron a cabo dos estudios cualitativos 17,18 para explorar las barreras de acceso a tratamiento para la DPP.…”
Section: Componente Cualitativounclassified
“…Uno de los estudios complementó estas entrevistas con observaciones realizadas en las salas de espera de los centros de salud y notas de campo 18 . Mayores detalles de los procedimientos específicos de selección de participantes, recolección de información y análisis de los datos fueron descritos previamente 17,18 .…”
Section: Componente Cualitativounclassified